Предмет: Алгебра, автор: JuliaO

6y+7  +8-5y=5
    4       3
  x+1  -   x-1  =   2   -   x+3
      4       6            2
 

Ответы

Автор ответа: piccina
0

6у+7/4   +   8-5у/3  =5

общ.знам 12

получается

3*(6у+7)  +  4*(8-5у)  = 12*5

18у+21+32-20у=60

-2у=7

у=-3,5

х-1/4 -  х+1/6  = 2-х+3/2

общ.знам. 12

получается

3*(х-1)-2*(х+1)=6*(2-х+3)

3х-3-2х-2=12-6х+18

х-5=30-6х

х+6х=30+5

7х=35

х=5

Автор ответа: Аноним
0

(6у + 7)/4 + (8 - 5у)/3 = 5

3(6у + 7)/12 + 4(8 - 5у)/12 = 5·12/12

3(6у + 7) + 4(8 - 5у) = 5·12

18у + 21 + 32 - 20у = 60

53 - 2у = 60

2у = -7

  у = -3,5

 

(х + 1)/4 - (х - 1)/6 = (2 - (х + 3))/2

3(х + 1)/12 - 2(х - 1)/12 = 6·2/12 - 6(х + 3)/12

3(х + 1) - 2(х - 1) = 6·2 - 6(х + 3)

3х + 3 - 2х + 2 = 12 - 6х - 18

х + 5 = -6 - 6х

7х = -11

х = -11/7

Похожие вопросы